Reconstructing Connectivism Theory in 21st Century Education - Rizki Fatullah; Ade Sudirman; Sholeh Hidayat (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
The rapid development of digital technology, artificial intelligence, and network-based learning environments has fundamentally transformed how knowledge is produced, distributed, and learned. This transformation exposes limitations in classical learning theories that were developed in relatively stable and linear educational contexts. Connectivism emerges as a theoretical response to these changes, emphasizing learning as a process of forming and maintaining connections within distributed knowledge networks. However, connectivism continues to face conceptual and practical criticism, particularly regarding its epistemological status and pedagogical applicability in formal education. This study aims to reconstruct connectivism theory within the landscape of 21st-century education by critically examining its challenges, identifying its pedagogical opportunities, and articulating its implications for contemporary teaching and learning practices. Using a critical literature review method, this article analyzes key national and international studies related to connectivism, digital pedagogy, and educational transformation. The findings indicate that connectivism remains highly relevant when reconceptualized as an integrative pedagogical framework that balances technological connectivity with cognitive, social, and ethical dimensions of learning. This reconstruction positions connectivism as a viable foundation for adaptive, reflective, and sustainable education in the digital era.